인제단층의 중생대 이 후 재활동 연대 - Chuluunbaatar Khulganakhuu(Chuluunbaatar Khulganakhuu); 송윤구(Yungoo Song); 정동훈(Donghoon Chung); 박창윤(Changyun Park); 최성자(Sung-Ja Choi); 강일모(Il-Mo Kang); 이기욱(Keewook Yi) (자원환경지질, 2015)
Recently developed illite-age-analysis(IAA) approach was applied to determine the fault-reactivated events for the Inje fault that cut through Precambrian biotite granitic gneiss with NNE-SSW trend in the middle of Korean peninsula. Three distinct fault-reactivated events of shallow crustal regime were recognized using the combined approach of optimized illite-polytype quantification and K-Ar age-dating of clay fractions separated from 4 fault clay samples: $87.0{±}0.12Ma$, $65.5{±}0.05$ and $66.6{±}1.38Ma$, $45.6{±}0.15Ma$, respectively. As well, $2M_1$ illite ages of 193~196 Ma and $254.3{±}6.96Ma$ were discernible, which may be related to the fault-activated time in the relatively deep crust. The study results suggest that the Inje fault would be firstly formed at $254.3^{°}$ ${æ}6.96Ma$ and sporadically reactivated in shallow regime since about 87 Ma. These reactivation events in shallow regime might be due to the Bulguksa orogeny that would be strongly influenced in Korean peninsula at that time. 본 연구에서는 한반도 중부지역 주요단층 중의 하나로 선캠브리아기의 흑운모 화강편마암을 절단하는 인제단층의 단층점토에 대한 IAA법 적용 및 해석을 통해 단층 재활동 절대연대를 결정하였다. 인제단층 홍천지점에서 채취된 4개 단층시료에 대한 K-Ar 연대측정 및 IAA 해석 결과, 3회($87.0{±}0.12Ma$, $65.5{±}0.05$ 및 $66.6{±}1.38Ma$, $45.6{±}0.15Ma$)의 뚜렷한 천부 단층 재활동연대가 확인되었다. 동일한 방법으로 결정된 193~196 Ma 및 $254.3{±}6.96Ma$의 $2M_1$ 일라이트 연대는 상대적으로 심부의 단층활동과 연관된 것으로 보인다. 본 연구결과들은 $254.3{±}6.96Ma$ 시기에 인제단층이 처음 생성되었을 가능성이 있으며, 약 87 Ma 이 후로는 천부 지각에서의 단층활동이 일어났었음을 제시한다. 약 87 Ma 이 후의 천부 지각 단층활동은 동 시기를 전후로 해서 한반도에 영향을 불국사 조산운동에 기인하는 것으로 생각된다.